KAYKOVUS’S WORK "NIGHTMARE" AND THE PROBLEM OF CHILDREN’S EDUCATION IN IT - Inomaliyeva Zilola Furqat qizi; Inomaliyeva Pokiza Furqat qizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article talks about the educational value of the work "Nightmare" written by Kaikovus and the human qualities related to the issue of raising children. The role of oriental manners in educating young people in the spirit of national values was discussed.